COVID-19 lockdown and its impact on tropospheric NO2 concentrations over India using satellite-based data. Issue 9 (September 2020) - Biswal, Akash; Singh, Tanbir; Singh, Vikas; Ravindra, Khaiwal; Mor, Suman
Abstract: The World Health Organization has declared the COVID-19 pandemic a global public health emergency. Many countries of the world, including India, closed their borders and imposed a nationwide lockdown. In India, the lockdown was declared on March 24 for 21 days (March 25–April 14, 2020) and was later extended until May 3, 2020. During the lockdown, all major anthropogenic activities, which contribute to atmospheric pollution (such as industries, vehicles, and businesses), were restricted. The current study examines the impact of the lockdown on tropospheric NO2 concentrations. Satellite-based ozone monitoring instrument sensor data were analyzed in order to investigate the variations in tropospheric NO2 concentrations. The results showed that from March 1 to 21, 2020, the average tropospheric NO2 concentration was 214.4 ×10 13 molecule cm −2 over India, and it subsequently decreased by 12.1% over the next four weeks. An increase of 0.8% in tropospheric NO2 concentrations was observed for the same period in 2019 and hence, the reduced tropospheric NO2 concentrations can be attributed to restricted anthropogenic activities during the lockdown. In the absence of significant activities, the contribution of various sources was estimated, and the emissions from biomass burning were identified as a major source of tropospheric NO2 during the lockdown. The findings of this study provide an opportunity to understand the mechanism of tropospheric NO2 emissions over India, in order to improve air quality modeling and management strategies. Abstract : Atmospheric Science; Air Quality; Environmental Analysis; Environmental Assessment; Environmental Pollution; COVID-19 lockdown; NO2 ; National Clean Air Programme; Biomass Burning; OMI